L'evolució de la llengua catalana al centre de l'antic Regne de València: reconquesta, immigració i canvi fonològic - Rasico, Philip D. (Caplletra. Revista Internacional de Filologia, 2015)
The author suggest sthe hypothesis that the «apitxat» orde voicing of the sibilants in the center of Valencia is due to the transfer of the voiceless phonemes, characteristic of the Aragonese and Castilian population living in Valencia during the Middle Ages, to Catalan.